2014
DOI: 10.1155/2014/478653
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Antitumor Effects of Platycodin D, a Saponin Purified from Platycodi Radix on the H520 Lung Cancer Cell

Abstract: Platycodin D is a major pharmacological constituent of Platycodi radix and has showed various pharmacological activities through oxidative stress defense mechanisms. Here, possible antitumor, anticachexia, and immunomodulatory activities of platycodin D were observed on the H520 tumor cell-bearing athymic nude mice after confirming the in vitro cytotoxicity. Platycodin D was orally administered at dose levels of 200, 100, and 50 mg/kg, once a day for 35 days from 15 days after implantation. The results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…As the principal active component in Platycodonis Radix, PD has been confirmed to have potential anticancer effects by inhibiting proliferation, inducing apoptosis, inducing cell cycle arrest, and blocking metastasis [9,10,[13][14][15]37] . This study provided evidence that PD inhibits cell proliferation of human hepatocellular carcinoma However, a decrease in body weight was observed during 10 mg/kg PD treatment ( Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the principal active component in Platycodonis Radix, PD has been confirmed to have potential anticancer effects by inhibiting proliferation, inducing apoptosis, inducing cell cycle arrest, and blocking metastasis [9,10,[13][14][15]37] . This study provided evidence that PD inhibits cell proliferation of human hepatocellular carcinoma However, a decrease in body weight was observed during 10 mg/kg PD treatment ( Figure 2C).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two mice died in the 10 mg/kg and 5 mg/kg PD-treated groups during the 21 d period, revealing that the intraperitoneal treatment with PD had toxic effects in BEL-7402 xenograft mice. More recently, oral administration of PD (50, 100, and 200 mg/kg) has been reported to reduce the tumor volumes in lung cancer H520 cell-bearing nude mice [37] . Thus, different administration methods of PD should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Park et al (2014) that PD in dosages of 50, 100, and 200 mg/kg exerted noticeable immunological enhancement and anti-cachexia effects on H520 tumor cell-bearing mice. In the present investigation, our results also showed that the thymus and spleen indices in all PD groups had no great significance compared to the vehicle control group.…”
Section: Discussionmentioning
confidence: 52%
“…As the most abundant triterpenoid saponin derived from the roots of Platycodin grandiflorum, Platycodin D (PD), has been reported to show a wide range of health benefits, such as anti-atherosclerotic (4), anti-inflammatory (5,6), hypocholesterolemic and anti-obesity effects (7). Previous studies have shown that PD has obvious anticancer activity against different human malignant cancer cells both in vitro (10,11,13,14,16,17) and in vivo (9,12,15).…”
Section: Discussionmentioning
confidence: 99%
“…Platycodin D (PD), a triterpenoid saponin derived from the roots of Platycodin grandiflorum, has been reported to possess a wide rangeof health benefits, such as anti-atherosclerotic (4), anti-inflammatory (5,6), hypocholesterolemic, and anti-obesity effects (7), as well as spermicidal and contraceptive activity (8). Among the various health benefits of PD, anticancer effects have been noted in several cancer cell lines, including lung cancer cells (9), hepatocellular carcinoma cells (10), gastric cancer cells (11), prostate cancer cells (12), and leukemia cells (13,14). PD has also been reported to inhibit the viability of human breast cancer cells in vitro (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%